Identification of cultivars of the forage legume Pueraria phaseoloides by electrophoretic patterns of storage proteins - Hussain, A.; Bushuk, W; Roca, W. (Springer, 1989)
A polyacrylamide gel electrophoresis procedure was developed for discriminating cultivars of the forage legume Pueraria phaseoloides on the basis of the patterns of cotyledon proteins. The genotypic marker proteins were extracted with 5M acetic acid and electrophoresed at pH 3.1 in aluminum lactate buffer. The procedure gave highly reproducible discrimination of ten selected cultivars.